Familial Resilience in Crisis: Navigating the Mediating Landscape of Depressive Symptoms Between Uncertainty Stress and Suicide Behavior Among Chinese University Students [Corrigendum] - Yan N; Zhou T; Hu M; Cai Y; Qi L; Shiferaw BD; Wang W; Miao C (Psychology Research and Behavior Management)
Yan N, Zhou T, Hu M, et al. Psychol Res Behav Manag. 2024(17):283-294. The authors have advised that the funding statement on page 292 is incorrect. The correct funding statement is as follows. FundingThis work was supported by the Education Science “14th Five-Year Plan” General Project in Jiangsu Province [D/2021/01/163] and Jiangsu Province Colleges “Qinglan” Project. The authors apologize for this error.